2017
DOI: 10.1016/j.bbagen.2017.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting sequence and stability information for directing nanobody stability engineering

Abstract: BackgroundVariable domains of camelid heavy-chain antibodies, commonly named nanobodies, have high biotechnological potential. In view of their broad range of applications in research, diagnostics and therapy, engineering their stability is of particular interest. One important aspect is the improvement of thermostability, because it can have immediate effects on conformational stability, protease resistance and aggregation propensity of the protein.MethodsWe analyzed the sequences and thermostabilities of 78 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 69 publications
1
47
0
1
Order By: Relevance
“…Previously, we had shown that the introduction of the sequence VE at positions 5 and 6 of an sdAb in combination with 1E or D, and 3Q could lead to an increase in Tm of 5–9 °C [ 32 , 33 ]. Other researchers examined a large repertoire of sdAb sequences and identified the changes 1E and 5V as stabilizing [ 34 ]. Also, prior studies have shown that the addition of negative charges can increase thermal stability and solubility of sdAbs [ 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we had shown that the introduction of the sequence VE at positions 5 and 6 of an sdAb in combination with 1E or D, and 3Q could lead to an increase in Tm of 5–9 °C [ 32 , 33 ]. Other researchers examined a large repertoire of sdAb sequences and identified the changes 1E and 5V as stabilizing [ 34 ]. Also, prior studies have shown that the addition of negative charges can increase thermal stability and solubility of sdAbs [ 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Despite the success of these and other approaches [ 47 , 49 , 50 , 51 , 52 ], stabilizing mutations in the CDRs or frameworks would be highly valuable. Fortunately, computational approaches for the design of antibodies with high affinity and thermostability have made significant recent advances [ 53 , 54 , 55 , 56 , 57 , 58 ].…”
Section: Physical and Chemical Stabilitymentioning
confidence: 99%
“…We sought to learn the constraints that characterize functional nanobodies by fitting the autoregressive model to a set of 1.2 million nanobody sequences from the llama immune repertoire (McCoy et al, 2014). Using this model, we find that length-normalized log-probability calculations predict the thermostability of new llama nanobody sequences (ρ=0.53, N=17; Figure 3a; Kunz et al, 2017).…”
Section: Generating An Efficient Library Of Functional Nanobodiesmentioning
confidence: 99%